2012
DOI: 10.1016/j.neurobiolaging.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

CSF α-synuclein does not differentiate between parkinsonian disorders

Abstract: Differentiating between Parkinson's disease (PD) and atypical Parkinsonism (AP) is clinically relevant but challenging. A timely and correct diagnosis might result in better targeted treatment strategies, adequate patient counseling, and early recognition of disease-specific complications. We aimed to investigate whether cerebrospinal fluid (CSF) concentrations of α-synuclein are of additional diagnostic value. We examined 142 consecutive patients with parkinsonism, mean disease duration 39.7 mo (Parkinson's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 4 publications
2
61
3
Order By: Relevance
“…These data were confirmed by personal studies [9], corroborating the opinion that CSF levels of tau may be a biomarker for the presence and severity of neurodegeneration [784,785], while others did not see such biomarker changes [786][787][788]. Other recent studies showed that CSF AS is currently unsuitable to differentiate between PD and atypical parkinsonism [789]. The source of PDlinked AS in human CSF remains unknown, but recent studies suggest that despite the higher levels in peripheral blood products, neurons in the CNS represent the principal source of AS in human CSF [790].…”
Section: α-Synuclein As a Biomarker For Synucleinopathiesmentioning
confidence: 52%
“…These data were confirmed by personal studies [9], corroborating the opinion that CSF levels of tau may be a biomarker for the presence and severity of neurodegeneration [784,785], while others did not see such biomarker changes [786][787][788]. Other recent studies showed that CSF AS is currently unsuitable to differentiate between PD and atypical parkinsonism [789]. The source of PDlinked AS in human CSF remains unknown, but recent studies suggest that despite the higher levels in peripheral blood products, neurons in the CNS represent the principal source of AS in human CSF [790].…”
Section: α-Synuclein As a Biomarker For Synucleinopathiesmentioning
confidence: 52%
“…CSF total-a-synuclein has ranged in previous studies from non-significant [13][14][15][16] to modest lowering in PD vs. controls [7][8][9][10][11][12]. Even though the lack of differences in CSF total a-synuclein in our study including for the first time iRBD patients might suggest that CSF total a-synuclein is not a premotor or diagnostic PD biomarker, the presence of significant MRI correlates of this CSF marker even in iRBD patients supports further longitudinal research of the combined use of CSF total a-synuclein and quantitative MRI (CTh) as candidate biomarkers of progression of iRBD to PD.…”
Section: Discussionmentioning
confidence: 99%
“…CSF total-a-synuclein levels in PD vs. controls have ranged in different studies from significant reductions [7][8][9][10][11][12] to similar levels [13][14][15][16]. Blood contamination of CSF has been pointed as a possible explanation for such discrepancies, but it remains unclear why among positive studies, some have needed controlling for CSF haemoglobin levels to find significant CSF total-a-synuclein reductions in PD [7,11], and some have not [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The small change in TNF-a mRNA levels in vivo contrasts dramatically with the levels of TNF-a protein induced in microglia in vitro by addition of the wild-type a-synuclein protein to the cultures (Su et al 2008), highlighting the differences between the gradual accumulation of mutant a-synuclein and the instantaneous addition to microglia in culture. These studies also raise the important question as to what is the appropriate concentration of a-synuclein to add to the cultured microglia, because the concentration that increased cytokine production was at least 10-fold higher than con-centrations found in the cerebrospinal fluid (Su et al 2008;Aerts et al 2011).…”
Section: Transgenic Modelsmentioning
confidence: 99%